Following the birth of the Italian Kingdom: Imposing or accepting the Italian language? - Panarello, Carmela (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
From the Middle Ages, the use of Italian language in literary production has contributed to hold together in a shared identity a people that still didn’t have a common army, law, and economy. Indeed, while being subjected to different dominations, the Italians had always been able to preserve their culture and traditions through language. In 1861, with the birth of the Italian Kingdom, it seemed natural to use the language to support the formation of a national consciousness. So, the Florentine language that was spoken by educated people, already used by Alessandro Manzoni in the last writing of the Promessi Sposi, was taken as a model to encode the newbirth common language.As a result, the element that in the past had been an incentive to cohesion, has now become an element of separation: the model of the Florentine language is opposed to the dialects spoken in various regions and to the educated people discourses on spoken language and literary language; the attempt to introduce in the state apparatus the terminology typical of the Kingdom of Sardinia, influenced by the Franco-Piedmontese dialect, is contrasted; but above all, the biggest obstacle to the wide diffusion of the new language was the difficulty, for most of the population still accustomed to dialects, to express themselves in Italian; furthermore for decades the school system couldn’t achieve, in the various regions, uniform results in the learning of the new language.